Penegakan Hukum terhadap Pelanggaran Perizinan Pengangkutan Bahan Bakar Minyak Bumi di Indonesia - Didit Firmansyah (Savana, 2025)
Violations of permits in the petroleum industry have significant impacts on legal, environmental, and economic aspects. In a legal context, these violations can result in administrative, criminal, and civil sanctions in accordance with the provisions stipulated in Law No. 22 of 2001 concerning Oil and Natural Gas and its derivative regulations. This study aims to determine the regulations governing it and how these regulations are implemented in the transportation of petroleum fuel in Indonesia. The method used is the normative legal method. The results of the study indicate that criminal acts of misuse of petroleum transportation and trade are regulated in the provisions of Article 55 of Law No. 22 of 2001 concerning Oil and Natural Gas which regulates the sanctions that will be obtained if they violate permits in illegal fuel transportation. In the licensing of petroleum fuel transportation, it shows that in the transportation of subsidized fuel, many individuals still do not have permits for the transportation of subsidized fuel, this is due to the lack of supervision, and the complexity of making these permits. In overcoming this crime, it is considered ineffective in its implementation for several reasons, one of which is that Law No. Law No. 22 of 2001 contains weaknesses and loopholes that allow perpetrators to escape justice. To address this, it is recommended to strengthen oversight through technology, simplify licensing procedures, and increase regulatory capacity. Furthermore, education and outreach are needed to encourage business compliance with applicable regulations. Firm and transparent law enforcement, along with public involvement in oversight, are also key to preventing similar violations in the future.